Airway Management in Disaster Response: A Manikin Study Comparing Direct and Video Laryngoscopy for Endotracheal Intubation by Prehospital Providers in Level C Personal Protective Equipment. Issue 4 (20th March 2017) - Yousif, Sami; Machan, Jason T.; Alaska, Yasser; Suner, Selim
Abstract: Introduction: Airway management is one of many challenges that medical providers face in disaster response operations. The use of personal protective equipment (PPE), in particular, was found to be associated with higher failure rates and a prolonged time to achieve airway control. Hypothesis/Problem: The objective of this study was to determine whether video laryngoscopy could facilitate the performance of endotracheal intubation by disaster responders wearing Level C PPE. Methods: In this prospective, randomized, crossover study, a convenience sample of practicing prehospital providers were recruited. Following standardized training in PPE use and specific training in the use of airway devices, subjects in Level C PPE were observed while performing endotracheal intubation on a stock airway in a Laerdal Resusci-Anne manikin system (Laerdal Medical; Stavanger, Norway) using one of three laryngoscopic devices in randomized order: a Macintosh direct laryngoscope (Welch Allyn Inc.; New York USA), a GlideScope Ranger video laryngoscope (Verathon Medical; Bothell, Washington USA), and a King Vision video laryngoscope (King Systems; Noblesville, Indiana USA). The primary outcome was time to intubation (TTI), and the secondary outcome was participant perception of the ease of use for each device. Results: A total of 20 prehospital providers participated in the study: 18 (90%) paramedics and two (10%) Emergency Medical Technicians-Cardiac. Participants took significantly longer when using the GlideScope Ranger [35.82 seconds (95% CI, 32.24-39.80)] to achieve successful intubation than with the Macintosh laryngoscope [25.69 seconds (95% CI, 22.42-29.42); adj. P<.0001] or the King Vision [29.87 seconds (95% CI, 26.08-34.21); adj. P=.033], which did not significantly differ from each other (adj. P=.1017). Self-reported measures of satisfaction evaluated on a 0% to 100% visual analog scale (VAS) identified marginally greater subject satisfaction with the King Vision [86.7% (SD=76.4-92.9%)] over the GlideScope Ranger [73.0% (SD=61.9-81.8%); P=.04] and the Macintosh laryngoscope [69.9% (SD=57.9-79.7%); P=.05] prior to adjustment for multiplicity. The GlideScope Ranger and the Macintosh laryngoscope did not differ themselves (P=.65), and the differences were not statistically significant after adjustment for multiplicity (adj. P=.12 for both comparisons). Conclusion: Use of video laryngoscopes by prehospital providers in Level C PPE did not result in faster endotracheal intubation than use of a Macintosh laryngoscope. The King Vision video laryngoscope, in particular, performed at least as well as the Macintosh laryngoscope and was reported to be easier to use. S Yousif, JT Machan, Y Alaska, S Suner .Airway management in disaster response: a manikin study comparing direct and video laryngoscopy for endotracheal intubation by prehospital providers in Level C personal protective equipment .Prehosp Disaster Med .2017 ;32 (4 ):352 –356 .